High resolution stratigraphy and miocene facies correlation in Lisbon and Setúbal Peninsula (Lower Tagus basin, Portugal) - Antunes, M. Telles (2010)
Correlation between facies associations (marine, estuarine and distal fluviatile environments) and disconformities, observed between Foz da Fonte (SW of Setúbal Peninsula) and Santa Iria da Azóia (NE of Lisbon) are presented. The precise definition of the marine-continental facies relationships improved very much the chronology of the depositional sequence boundaries. Tectonic and eustatic controls are discussed on the basis of subsidence rates variation.